ANALYSIS OF FUNDRAISING STRATEGIES IN THE AL-QUR’AN EDUCATIONAL PARK - Almafahir, Ahmad (Jurnal Isema : Islamic Educational Management, 2023)
Fundraising is one solution to bridge the financial gap and ensure the continuity of educational programs. This research aims to determine the fundraising strategy to increase community awareness carried out by TPQ Darussalam Tambakaji Ngaliyan Semarang. This research uses a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, in-depth interviews, documentation studies, and data analysis through data unitation, categorization, and interpretation. The research results revealed that the strategy used to increase community awareness at the TPQ Darussalam institution was by providing hospitality to residents, installing banners and pamphlets, and presenting students at Islamic Holiday Commemoration (PHBI) events. The funds came from residents, parents, donors, and class charity boxes. This strategy has been effective enough to meet the institution's operational needs.